Doctoral Student of Fergana Polytechnic Institute - Tukhtashev Farrukhjon Esonali ugli (Web of Journals Publishing, 2023)
Therefore, it is necessary to continue scientific research on the scientific basis of development of acceptable norms and periods of application of various chemical agents in each created cotton variety. The optimal recommendations for the production of cotton in the soil-climatic conditions of the Fergana region based on the study of the duration and norms of feeding cotton with liquid nitrogen fertilizers on the growth, development and productivity of the plant giving is the main goal of the research.
Keywords: Liquid fertilizer, harvest elements, wheat, grain, cob, crop branch, cotton, fertility, suspension, flower, complex fertilizer, mineral fertilizers nitrogenous fertilizers.